Expanding the Repertoire of the Plant-Infecting Ophioviruses through Metatranscriptomics Data - Debat, Humberto Julio; Garcia, Maria Laura; Bejerman, Nicolas Esteban (MDPI, 2023)
Ophioviruses (genus Ophiovirus, family Aspiviridae) are plant-infecting viruses with non-enveloped, filamentous, naked nucleocapsid virions. Members of the genus Ophiovirus have a segmented single-stranded negative-sense RNA genome (ca. 11.3–12.5 kb), encompassing three or four linear segments. In total, these segments encode four to seven proteins in the sense and antisense orientation, both in the viral and complementary strands. The genus Ophiovirus includes seven species with viruses infecting both monocots and dicots, mostly trees, shrubs and some ornamentals. From a genomic perspective, as of today, there are complete genomes available for only four species. Here, by exploring large publicly available metatranscriptomics datasets, we report the identification and molecular characterization of 33 novel viruses with genetic and evolutionary cues of ophioviruses. Genetic distance and evolutionary insights suggest that all the detected viruses could correspond to members of novel species, which expand the current diversity of ophioviruses ca. 4.5-fold. The detected viruses increase the tentative host range of ophioviruses for the first time to mosses, liverwort and ferns. In addition, the viruses were linked to several Asteraceae, Orchidaceae and Poaceae crops/ornamental plants. Phylogenetic analyses showed a novel clade of mosses, liverworts and fern ophioviruses, characterized by long branches, suggesting that there is still plenty of unsampled hidden diversity within the genus. This study represents a significant expansion of the genomics of ophioviruses, opening the door to future works on the molecular and evolutionary peculiarity of this virus genus.